Human Induced Pluripotent Stem Cell-Derived Cardiac Progenitor Cells in Phenotypic Screening: A Transforming Growth Factor-β Type 1 Receptor Kinase Inhibitor Induces Efficient Cardiac Differentiation. (18th December 2015) - Drowley, Lauren; Koonce, Chad; Peel, Samantha; Jonebring, Anna; Plowright, Alleyn T.; Kattman, Steven J.; Andersson, Henrik; Anson, Blake; Swanson, Bradley J.; Wang, Qing-Dong; Brolen, Gabriella
Abstract : To understand and exploit cardiac ontogeny for drug discovery efforts, an in vitro human induced pluripotent stem cell-derived cardiac progenitor cell (CPC) model system was developed using a highly enriched population of KDR pos /CKIT neg /NKX2.5 pos CPCs. These CPCs were capable of generating highly enriched cultures of cardiomyocytes under directed differentiation conditions. The suitability of these cells for medium- to high-throughput screens to assess both proliferation and multilineage differentiation was demonstrated, and utility of the screen was highlighted with the identification of novel inducers of differentiation. Abstract: : Several progenitor cell populations have been reported to exist in hearts that play a role in cardiac turnover and/or repair. Despite the presence of cardiac stem and progenitor cells within the myocardium, functional repair of the heart after injury is inadequate. Identification of the signaling pathways involved in the expansion and differentiation of cardiac progenitor cells (CPCs) will broaden insight into the fundamental mechanisms playing a role in cardiac homeostasis and disease and might provide strategies for in vivo regenerative therapies. To understand and exploit cardiac ontogeny for drug discovery efforts, we developed an in vitro human induced pluripotent stem cell-derived CPC model system using a highly enriched population of KDR pos /CKIT neg /NKX2.5 pos CPCs. Using this model system, these CPCs were capable of generating highly enriched cultures of cardiomyocytes under directed differentiation conditions. In order to facilitate the identification of pathways and targets involved in proliferation and differentiation of resident CPCs, we developed phenotypic screening assays. Screening paradigms for therapeutic applications require a robust, scalable, and consistent methodology. In the present study, we have demonstrated the suitability of these cells for medium to high-throughput screens to assess both proliferation and multilineage differentiation. Using this CPC model system and a small directed compound set, we identified activin-like kinase 5 (transforming growth factor-β type 1 receptor kinase) inhibitors as novel and potent inducers of human CPC differentiation to cardiomyocytes. Significance: Cardiac disease is a leading cause of morbidity and mortality, with no treatment available that can result in functional repair. This study demonstrates how differentiation of induced pluripotent stem cells can be used to identify and isolate cell populations of interest that can translate to the adult human heart. Two separate examples of phenotypic screens are discussed, demonstrating the value of this biologically relevant and reproducible technology. In addition, this assay system was able to identify novel and potent inducers of differentiation and proliferation of induced pluripotent stem cell-derived cardiac progenitor cells.